Mekanisme Pengurusan Mutasi Jabatan Crew Kapal pada Kantor KSOP Kelas I Dumai oleh PT. Samudera Sarana Karunia Dumai - Yolanda Breka Br Brahmana; Yursal Yursal; Yuna Sutria (Politeknik Pelayaran Sulawesi Utara, 2025)
This study aims to analyze the mechanism for managing ship crew position mutations at the Class I Harbor Master and Port Authority (KSOP) Office in Dumai, conducted by PT. Samudera Sarana Karunia Dumai. As a shipping agency, PT. Samudera Sarana Karunia plays a vital role in ensuring the administrative legality of personnel changes on board. The research method employed is descriptive qualitative, utilizing data collection techniques such as field observations and library research by reviewing maritime regulations and human resource management theories. The results indicate that the mutation mechanism involves several stages: application submission, competency document verification, institutional approval, and the sign-on/sign-off process in the seafarer's discharge book. Despite established procedures, several obstacles were identified, including administrative delays, incomplete supporting documents, and a lack of understanding among crew members regarding the applicable mutation procedures. These issues lead to operational time inefficiencies for the vessel at the port. The study concludes that strengthening coordination between the agency and the crew, along with meticulous document validation, is essential to streamline the position mutation process and support the vessel's seaworthiness.